Simultaneous determination of lesinurad and co-administered drugs used in management of gout comorbidities to uncover potential pharmacokinetic interaction in rat plasma - Hadeel A. Khalil; Amira F. El-Yazbi; Eman I. El-Kimary; Mohamed A. Elrewiny; Ahmed F. El-Yazbi; Tarek S. Belal (Scientific Reports)
Abstract Gout is one of the most prevalent forms of arthritis that is usually accompanied by other comorbidities. For this reason, multiple drugs are routinely prescribed for gout patients, which may affect the clinical course outcomes, and increase the risk of drug-drug interactions. This work presents a novel, simple, and sensitive high performance liquid chromatography (HPLC) method for the simultaneous determination of lesinurad (LES) and other co-administered drugs that are subject to potential pharmacokinetic interactions such as etoricoxib (ETC), eplerenone (EPL), and amiodarone (AMD) in rat plasma. Moreover, a pharmacokinetic study was conducted by co-administration of LES and ETC to rats to assess any possible alteration in their pharmacokinetic profiles and the obtained samples were analyzed using the developed method. Chromatographic separation was achieved using a gradient elution of a mobile phase consisting of acetonitrile and potassium dihydrogen orthophosphate buffer, pH 4.2 on a Zorbax Eclipse Plus C18 (4.6 × 250 mm, 5 μm particle size) column. The developed method exhibits adequate sensitivity with a LLOQ of 100 ng/mL and was successfully validated as per the FDA bioanalytical guidelines and was found to be linear over the range from 100 to 50,000 ng/mL for all the selected drugs. The results of the pharmacokinetic study showed an increase in the area under the curve (AUC) of each of the two drugs (LES and ETC) following the repeated administration of the other. This raises concerns of the possible renal injurious effect of ETC when co-prescribed with LES. Moreover, this work uncovers the necessity for therapeutic dose adjustment or increased clinical vigilance for side effects and/or lack of efficacy upon concomitant administration of the selected drugs to gout patients.